General Geology of Bukit Tinggi Area, Pahang with emphasis on Bukit Tinggi Fault Zone - bt Suharto, Nur Shafiqah Athirah (Universiti Teknologi PETRONAS, 2016)
Bukit Tinggi is an area located at the southwest of Pahang and bounded by Bukit Tinggi Fault Zone and Kuala Lumpur Fault Zone. However, there is lack of correlation between the rock physical characteristics with Bukit Tinggi Fault Zone, as the available research does not thoroughly provide detailed geological properties of the rocks at Bukit Tinggi. It is known that generally, Bukit Tinggi area is dominated by igneous (Main Range Granite) and metamorphic rocks but different lithology occur at the different outcrops and it is best to compare the lithology of Janda Baik area with Bukit Tinggi area. The methodologies that are used in the research are listed down based on the scale of observation that includes microscopic (thin section analysis), mesoscopic (field and hand sample observation), and megascopic (regional study through Digital Elevation Model). The methodologies are significant to identify the detailed mineralogy and petrography of the rocks as well as the structural study of Bukit Tinggi area. From the fieldwork, overall there are total of six outcrops at Bukit Tinggi and four at Janda Baik area. At Bukit Tinggi, the igneous rocks are felsic igneous rocks which are fine to coarse-grained biotite porphyritic granite, porphyritic microgranite and granitic gneiss. The rocks also show two-phase variant granite occurrence. Meanwhile, Janda Baik area show medium-grained characteristic of biotite granite lithology. From the study, the minerals are comprised of K-Feldspar, plagioclase, quartz, biotite and chlorite. Major faults and fracture trends in this area include NNW-SSE, N-S, NW-SE, and E-W. Wide distribution of Bukit Tinggi strike slip faults interpreted occurred in the earliest phase followed by normal faulting and then reverse fault took place (Zainal Abidin et. al, 2010). The study provided more detailed findings compared to the previous studies.